Catheter ablation versus antiarrhythmic drugs as first-line therapy for symptomatic atrial fibrillation: a systematic review and meta-analysis. (24th May 2021) - Casula, M; Pignalosa, L; Fortuni, F; Baldi, E; Sanzo, A; Savastano, S; Petracci, B; Vicentini, A; Rordorf, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: In patients with symptomatic atrial fibrillation (AF), current international guidelines favor the use of antiarrhythmic drugs (AAD) as initial therapy for the maintenance of sinus rhythm. Previous studies have compared catheter ablation for pulmonary vein isolation versus AAD in this clinical scenario but the best first-line therapeutic option in patients with symptomatic AF candidates for rhythm control strategy remains an open issue. Aim To compare efficacy and safety of catheter ablation versus AAD as first-line therapy in patients with symptomatic AF. Methods: We searched electronic databases for randomized controlled trials (RCTs) comparing catheter ablation versus AAD as first-line therapy for symptomatic AF. The primary efficacy outcome was any recurrence of atrial tachyarrhythmias. The secondary efficacy outcomes were symptomatic arrhythmic recurrences. The safety outcomes were serious adverse events related to the therapeutic regimen. Outcome events were defined according to the definition used in each original study. The effect size was estimated using a random-effect model as risk ratio (RR) and relative 95% confidence interval (CI) with the statistical software Review Manager 5.3. Results: Five RCTs counting 997 patients (503 treated with catheter ablation and 494 with AAD) were included in the analysis. Mean age was 57 ± 3 years, 30% were female. Mean left ventricle ejection fraction was 60%±4% and mean left atrial diameter was 40 mm ± 1 mm. At baseline 52% of patients were treated with a beta-blocker and 11% with a calcium channel blocker. In the catheter ablation group 258 patients (51%) underwent cryoablation and 245 (49%) radiofrequency ablation. Median follow-up was 12 months (IQR 12-24 months). Patients treated with catheter ablation had statistically significant lower risk of atrial tachyarrhythmias recurrences (RR 0.59; 95%CI 0.45-0.76; p < 0.0001 – Figure A) and of symptomatic arrhythmia recurrences (RR 0.45; 95%CI 0.25-0.80; p = 0.007 – Figure B) compared with those treated with AAD. The risk of serious adverse events related to the therapeutic regimen did not differ significantly between patients undergoing catheter ablations and those treated with AAD (RR 0.85; 95%CI 0.45-1.59 – Figure C). Conclusions: In patients with symptomatic AF, catheter ablation as first-line therapy is associated with a reduced risk of atrial tachyarrhythmias recurrences compared with AAD, without statistically significant differences in the risk of serious adverse events related to the treatment.